2018
DOI: 10.1002/em.22244
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mitochondrial DNA copy number and damage in a mercury‐exposed rural Peruvian population near artisanal and small‐scale gold mining: An exploratory study

Abstract: Mitochondrial DNA (mtDNA) copy number (CN) and damage in circulating white blood cells have been proposed as effect biomarkers for pollutant exposures. Studies have shown that mercury accumulates in mitochondria and affects mitochondrial function and integrity; however, these data are derived largely from experiments in model systems, rather than human population studies that evaluate the potential utility of mitochondrial exposure biomarkers. We measured mtDNA CN and damage in white blood cells (WBCs) from 83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 81 publications
2
9
0
1
Order By: Relevance
“…2C-D ), as well as promoter hypermethylation of the RIG-1 signaling pathway ( Supplemental Table S4 ) through which DAMPs trigger innate immune responses 139 . Although prior papers have not reported clear associations between mitochondrial biomarkers and MeHg exposure, it was unclear whether this lack of signal was statistical or biological 140,141 . The clear signal in immune signaling pathways in our data, coupled with the lack of association between mitochondrial biomarkers and MeHg, indicates that the biological role of mitochondria in the response to MeHg is more complex than previously thought.…”
Section: Discussionmentioning
confidence: 97%
“…2C-D ), as well as promoter hypermethylation of the RIG-1 signaling pathway ( Supplemental Table S4 ) through which DAMPs trigger innate immune responses 139 . Although prior papers have not reported clear associations between mitochondrial biomarkers and MeHg exposure, it was unclear whether this lack of signal was statistical or biological 140,141 . The clear signal in immune signaling pathways in our data, coupled with the lack of association between mitochondrial biomarkers and MeHg, indicates that the biological role of mitochondria in the response to MeHg is more complex than previously thought.…”
Section: Discussionmentioning
confidence: 97%
“…difference in averages between three different communities in Peru, despite high variability within each community [56], indicating that a significant portion of the variability was nonrandom. Second, in the current study, we identified two individuals with a surprisingly low mtDNA CN values.…”
Section: Plos Onementioning
confidence: 98%
“…Besides chemical pollutants, blood, and urine samples were also analysed for other physiological parameters, such as blood lactate and cyanide [73,74], haematological parameters, and other blood chemistry [47,75], mitochondrial DNA, and other DNA mutations [48,[76][77][78], immunological response to vaccines, and other immune-related proteins [50,79,80], renal and respiratory parameters [75,81], and infectious diseases, such as malaria [82] and HIV [47,83]. Saliva (cortisol salivary) [84], Buccal cells (DNA damage and mutations) [63,77], and stool samples (soil-transmitted helminths and Vibrio cholerae) [85,86] were also reported.…”
Section: Human Samples and Related Biomarkersmentioning
confidence: 99%